Reconstructing the Theory of Production within the Islamic Economic Paradigm: A Normative and Applied Study - Rahmawati Rahmawati; Abdul Wahab; Wahyuddin Abdullah (Jurnal Ekonomi Balance, 2025)
Islamic economics refers to an economic system founded on the principles and structure of the Qur’an and the Sunnah, with the ultimate aim of achieving maslahah (public benefit) for humanity. Conceptually and in principle, Islamic economics is fixed; however, in practice, it can be flexible and adaptive depending on specific circumstances and conditions. The fundamental principles of Islamic economics can be summarized into four key values: tawhid (monotheism), balance, free will, and responsibility. Production in Islamic economics is not merely the physical creation of something new, but also the process of adding utility to goods through various productive activities. The ultimate goal of production is to achieve happiness in both this world and the hereafter, in line with the objectives of maqasid al-shari’ah. These objectives dictate that production activities must be based on Islamic values, ensuring that the goods or services produced do not contradict the preservation of religion, life, intellect, lineage, and wealth. Production priorities should align with the hierarchy of needs: dharuriyyat (essentials), hajiyyat (complementary needs), and tahsiniyyat (refinements). Moreover, production must account for aspects such as justice, social welfare, zakat, charity (sadaqah), almsgiving (infak), and endowments (waqf). It should also ensure optimal management of natural resources, avoid waste and excess, and prevent environmental degradation. A fair distribution of profits among owners, managers, and employees must also be maintained. Production cannot be separated from the factors of production, which include natural resources (land), labor, capital, management, technology, and raw materials.